Factors Influencing User Behavior in Hospital Management Information System at the Emergency Department of Dr. Moewardi Regional Hospital - Putri Utami Yuniati; Sri Sugiarsi; Rohmadi; Harjanti (Indonesian Journal of Health Information Management, 2025)
AbstractAccording to Minister of Health Regulation Number 82 Year 2013, Hospital Management Information System (HMIS) is a communication technology information system that processes and integrates the entire hospital service process flow in the form of coordination networks, reporting, and administrative procedures to obtain precise and accurate information, and it is part of the Health Information System. Behavior is closely related to a system; a system is considered successful if users do not reject it. To prevent users from rejecting a system, it is necessary to establish good technical quality of information technology systems (Jogiyanto, 2007). To assess the quality of HMIS, research and evaluation related to user behavior of HMIS are necessary. Research on information technology user behavior includes several models, one of which is The Unified Theory of Acceptance and Use of Technology (UTAUT). Dr. Moewardi Regional General Hospital has long implemented web-based HMIS. HMIS at Dr. Moewardi Regional Hospital has been operational since 2018 in the Outpatient, Inpatient, and Emergency units, hence the need for HMIS evaluation. The objective of this study is to determine the factors influencing user behavior in hospital management information systems at the Emergency Installation of Dr. Moewardi Regional Hospital. The study population consists of HMISusers in the Emergency Department. Data analysis was conducted using multiple linear regression method, yielding the following results: variabels that partially positively influence HMIS user behavior are performance expectancy with sig T-test value 0.024 < 0.05; effort expectancy with sig Ttest value 0.008 < 0.05; facilitating conditions with sig T-test value 0.021 < 0.05. The variabel of Social Influence does not partially influence HMIS user behavior with sig T-test value 0.088 > 0.05. Simultaneously, the variabels of performance expectancy, effort expectancy, Social Influence, and facilitating conditions positively influence HMIS user behavior with sig F-test value 0.000 < 0.05.Keywords: HMIS, UTAUT model